Clinical reporting following the quantification of cerebrospinal fluid biomarkers in Alzheimer's disease: An international overview. Issue 10 (22nd December 2021) - Delaby, Constance; Teunissen, Charlotte E.; Blennow, Kaj; Alcolea, Daniel; Arisi, Ivan; Amar, Elodie Bouaziz; Beaume, Anne; Bedel, Aurélie; Bellomo, Giovanni; Bigot‐Corbel, Edith; Bjerke, Maria; Blanc‐Quintin, Marie‐Céline; et al.
Abstract: Introduction: The current practice of quantifying cerebrospinal fluid (CSF) biomarkers as an aid in the diagnosis of Alzheimer's disease (AD) varies from center to center. For a same biochemical profile, interpretation and reporting of results may differ, which can lead to misunderstandings and raises questions about the commutability of tests. Methods: We obtained a description of (pre‐)analytical protocols and sample reports from 40 centers worldwide. A consensus approach allowed us to propose harmonized comments corresponding to the different CSF biomarker profiles observed in patients. Results: The (pre‐)analytical procedures were similar between centers. There was considerable heterogeneity in cutoff definitions and report comments. We therefore identified and selected by consensus the most accurate and informative comments regarding the interpretation of CSF biomarkers in the context of AD diagnosis. Discussion: This is the first time that harmonized reports are proposed across worldwide specialized laboratories involved in the biochemical diagnosis of AD.